Design of experiment studies for the fabrication processes involved in the micro-texturing of surfaces for fluid control - Wallis, Kirsty (Cranfield University, 2013)
This thesis focuses on the use of a design of experiment approach to examine the significance of process factors and interactions on the fabrication of micro- textured surfaces. The micro-textured surfaces examined contain pillar and hole features ranging from 80 – 2 micrometers in diameter. The processes examined are the deep reactive ion etching of silicon wafers for the production of silicon mould inserts and the micro-injection moulding of polypropylene, high density polyethylene and 316LS stainless steel replicate samples of the silicon mould insert. During the deep reactive ion etching of the silicon wafers the design of experiment approach was used to determine the significant of platen power, C4F8 gas flow and switching times to the presence of pillar undercut of 10 x 10, 5 x 5 and 2 x 2 micrometer pillars. Undercuts occur when the pillar base has a smaller cross-section than the apex of the pillar. Switching times was found to be the only statistically significant parameter for both 10 x 10 and 5 x 5 micrometer pillars. The design of experiment approach is used in the micro-injection moulding of polypropylene, high density polyethylene and 316LS stainless steel replicates to examine the significance of mould temperature, cooling time, holding pressure and injection speed on the part and buffer mass of the produce samples, the height and width of pillar on the replicate surfaces and the variation of the replicated pillars height and width from the original silicon mould insert. Examination of the high density polyethylene replicates found that mould temperature was the most significant factor regarding pillar dimensions (and variation from the silicon mould insert) across the range of pillar sizes. Upon examination of the polypropylene replicates it was found that the factor of most significance on pillar dimensions varied across the different pillar sizes. Holding pressure was identified as the most significant factor with regards to the 53 x 29 and 19 x 80 micrometer pillars. Injection speed was found to be most significant for the 25 x 25 and 19 x 29 micrometer pillars. Cooling time was found to be most significant with regards to the 30 x 10, 25 x 10, 20 x 10 and 15 x 10 micrometer pillars. While ii mould temperature was found to be most significant for the 20 x 20, 15 x 15 and 10 x 30 micrometer pillars. The interaction between mould temperature and injection speed was also found to be the most significant factor with regards to the 43 x 29 and 25 x 30 micrometer pillars. Examination of the 316LS replicates found that mould temperature was the most significant factor regarding pillar dimensions for 80 x 80 and 19 x 80 micrometer pillars. While holding pressure was found to be most significant to the 29 x 29 micrometer pillars and injection speed was identified as most significant to the 53 x 80 micrometer pillars. The samples produced during the design of experiment investigations were then used to examine the effect of surface texturing on droplet behaviour. Droplet contact angles were examined on polypropylene, high density polyethylene and silicon samples structured with 10 – 2 micrometer pillar. Initial droplet contact angles were found to be higher on the polypropylene samples than the high density polyethylene or silicon samples. With the lowest initial contact angles being found for the silicon inserts. Droplet ‘channelling’ and evaporation were examined on silicon, polypropylene, high density polyethylene and 316LS samples structured with micro-channel surface pillars and holes ranging from 80 – 2 micrometer in diameter. Contact pinning of the droplet to the surface via the three- phase contact-line was noted during observations of droplet ‘channelling’. This pinning effect was observed at all sample tilt angles (30 - 90 o ). With regards to droplet evaporation, the droplets were noted to evaporate evenly (with no or limited contact pinning) on all unstructured surfaces and the surfaces structured with hole features. On the surfaces structured with pillar features, the droplets appeared too evaporated along the surface gradient from the smallest pillars to the largest.
Keywords: Design of experiment; deep reactive ion etching; polymer micro-injection moulding; metal powder injection moulding; droplet behaviour; contact angles; evaporation